Research Infographic: An Innovative Instructional System Design Teaching Steps In Writing a Research Paper - Corcega, Kristin Anne (JPAIR Institutional Research, 2019)
Research is viewed as a complex subject matter for students of all levels and various disciplines, as observed by the Research Center of the Dalubhasaan ng Lunsod ng San Pablo (DLSP). According to the pre-test conducted, 62% of the Grade 11 students in DLSP Integrated School answered that they do not like research as a subject. Moreover, 94% of students answered that they do not wish to learn more about research. Naturalistic observation suggests a better alternative to conventional classroom teaching strategies. An infographic ISD module was conceptualized using the ADDIE Model. After being exposed to the ISD module, more of the target learners were able to identify and analyze the steps in writing a research paper. Using McNemar’s test, there was a significant difference in the target learners’ idea in steps in making a research paper, with a staggering result of p= .000. A significant difference was detected in the student’s desire to learn more about research after viewing the ISD module with the pre-and post-intervention of p= .017. Some of the generalizations are; there is nothing to improve in the ISD module because it is what they need to learn about research, and it is informative and easy to understand. An additional criterion of the ISD module effectivity was contributed by the reported performance evaluation of the target learners. Their final research outputs scored 85% - 93% as an average rating.